Minutes of Proceedings of Bd. of Comm’rs of Central Park, N.Y. for Year Ending April 30, 1858, at 166 - (:unkn) unknown (General Publisher, 1858)
Prohibited the carry of firearms, throwing stones or other missiles within Central Park.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES